Arbitrage des phoques à fourrure - United States.; Bering Sea Tribunal of Arbitration. (Paris, Typographie Chamerot et Renouard, 1893)
Issued also in Paris in 1893 by Welter [Imprimerie nationale] for the French ministry of foreign affairs. The original English texts comprise v. 1 and the first parts of volumes 7 and 9 of the complete Proceedings, 16 v., Washington, 1895. Arguments of the United States before the Bering Sea tribunal of arbitration which met in Paris in accordance with the treaty concluded February 29, 1892 between the United States and Great Britain. [v. 1] Mémoire.--[v. 2] Contre-mémoire.--[v. 3] Plaidsyer. Mode of access: Internet.